Electrophysiological verification of enhanced S-cone syndrome caused by a novel c.755T>C NR2E3 missense variant. (2nd January 2019) - Cehajic-Kapetanovic, Jasmina; Cottriall, Charles L.; Jolly, Jasleen K.; Shanks, Morag; Clouston, Penny; Charbel Issa, Peter; MacLaren, Robert E.
ABSTRACT: Background : Nuclear hormone receptor gene, NR2E3, plays a critical role in retinogenesis and determination of the rod photoreceptor phenotype. Mutations in NR2E3 typically lead to recessive enhanced S-cone syndrome (ESCS), where affected individuals show higher sensitivity to short wavelength light and early onset rod dysfunction. Patients with ESCS present in early childhood with nyctalopia, enhanced sensitivity to blue light and display a very heterogeneic retinal phenotype with varying degrees of clumped pigmentation and occasional retinoschisis. Purpose : To confirm the pathogenicity of a novel mutation in NR2E3 using electrophysiological studies. Materials and Methods : Patient underwent detailed clinical evaluation and ophthalmic imaging followed by next generation sequencing analysis and electrophysiological studies. Results : We describe a case of a young man of Greek descent with a family history of retinal degeneration. His fundal features at presentation were atypical of ESCS, with striking macular involvement in both eyes, including fibrotic subretinal material overlying the pigment epithelial detachment in one eye and schisis in the other. Genetic testing revealed a novel homozygous variant in NR2E3 gene of uncertain pathogenicity. Instead of performing further genetic analyses, electrophysiological studies showed pathognomonic changes in the S-cone response. Conclusions : With the recent clinical endorsement of a gene therapy for RPE65 related-inherited retinal degeneration it is of paramount importance to correctly identify the pathogenic genetic mutation. In this particular syndrome, we highlight the value of electrophysiology to confirm the pathogenicity of a novel mutation in NR2E3 and aid the diagnosis of ESCS, with potential for gene therapy in the future.